A facile and cost-effective approach to fabricate flexible graphene films for aqueous available current collectors. (December 2020) - Mu, Zhipeng; Liu, Ting; Ji, Xu; Luo, Haowei; Tang, Lujie; Cheng, Shuang
Abstract: Aqueous energy storage devices have been widely considered because of their advantages in such aspects as security, cost and ionic conductivity. Yet, current collectors that can be used in water systems are very limited. Herein, a convenient and cost-effective approach to fabricate flexible graphene films (FGFs) that can be used as aqueous available current collectors is developed. Firstly, very thin graphene nanoplatelets are prepared in a very short time (less than 6 h) at room temperature by optimizing the ratio of H2 O2 and concentrated H2 SO4 using natural graphite flake as raw material. The as-obtained graphene nanoplatelets are subsequently shaped into FGFs through a simple roll pressing technique. Compared with commercial carbon cloth (CC) and carbon paper (CP), the FGF possesses obvious better hydrophilicity and higher conductivity of 2.56 × 10 5  S/m together with lighter area weight. In alkaline solution, commercial activated carbon loaded on the FGF exhibits better electrochemical performance than that on CC or CP. The FGF fabrication approach developed here is efficient, economical and feasible, making it ideal for bulk production as water available current collectors. Graphical abstract: Image 1